Rancang Bangun Purwarupa Alat Pencitraan Gerak Model Gestur Berbasis Mikrokontroler Arduino - Akbar, Firman Aulia; Kurnia, Mega Tri; Sarimole, Frencis Matheos (FIKOM Universitas Bung Karno, 2023)
In the era of rapidly developing technology, the integration between body and technology becomes real, especially in the development of human and computer interaction. This research focuses on creating prototypes of motion imaging tools using microcontroller technology, responding to the need for more intuitive interactive tools in translating human movements. Using hardware and software engineering approaches, this study designed and tested a tool consisting of Gyrometer and Flex sensors. The gyrometer measures the orientation of motion, while the Flex sensor detects the curvature of the gesture. Tests include calibration between sensors, integration with the HC-05 Bluetooth transmission module as a wireless communication medium, and applications installed on smartphones as processing output information . The study introduced a method of gesture imaging of gestures, providing a solution to interact with computers more naturally. The urgency of this research answers the need to help translate human movement into digital input. The modeled tool is able to detect hand gestures with good accuracy. The smartphone as an output successfully displays information in the form of text and voice based on detected movements. This gesture model motion imaging tool successfully passed the testing stage, showing the effective results of the Gyrometer and Flex sensors in detecting and translating hand movements. The Bluetooth module as a data transmitter runs well sending data to an application on the smartphone, which then displays the information accurately.